The photoelectrocatalytic oxidative treatment of textile wastewater containing disperse dyes - Paschoal, Fabiana M. M. [UNESP]; Anderson, Marc. A.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2009)
This paper presents a study of a prospective photoeletrocatalytic oxidation treatment system for disperse dyes obtained from a textile industry. The process utilizes titanium dioxide thin-film electrodes prepared by the sol-gel method as a photo-oxidative anode. Using UV irradiation and ail applied potential of + 1.0 V on the nanoporous photoanode of Ti/TiO(2) it is Possible to reach a reduction of color removal of 90%, 94% and 100% and 63%, 45% and 61% for TOC removal of DOD, DRD and DRR dyes. The method has been successfully applied to treat textile industry effluent collected at different steps in the industrial process namely before and after conventional wastewater treatment. The results were satisfactory for both effluent samples, leading to a reduction from 52.6% to 69.0% of COD, a diminishing of 80-89% of discoloration and a removal of TOC in the range of 47 to 50%. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Photoelectrocatalytic oxidation; Textile industry; Disperse dyes; Textile wastewater; Photoelectrochemistry; Textile effluent